Pengaruh Rasio Kemandirian, Rasio Efektivitas PAD, Rasio Efisiensi Belanja, dan Rasio Efisiensi Keuangan terhadap Dana Insentif Fiskal pada Pemerintah Provinsi di Indonesia - Nadiyya Amanda Putri; Bainil Yulina; Yevi Dwitayanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The study aims to determine the effect of the Independence Ratio, the PAD Effectiveness Ratio, the Expenditure Efficiency Ratio, and the Financial Efficiency Ratio on Fiscal Incentive Funds partially and simultaneously in Provincial Governments in Indonesia in 2021-2023. The type of data used in this study is secondary data obtained from Provincial LKPD data in Indonesia for the 2021-2023 period sourced from the official website of the Supreme Audit Agency of the Republic of Indonesia (BPK RI). The method in this study is quantitative. The population in this study was 38 Provinces in Indonesia and used a purposive sampling technique to obtain a sample of 20 Provinces. The data analysis technique applied for this study was multiple linear regression analysis using IBM SPSS Version 26. The results of the study show that the Independence Ratio and the PAD Effectiveness Ratio have a positive and significant effect on Fiscal Incentive Funds, the Expenditure Efficiency Ratio has a negative and significant effect on Fiscal Incentive Funds, while the Financial Efficiency Ratio has no effect on Fiscal Incentive Funds. The Independence Ratio, PAD Effectiveness Ratio, Expenditure Efficiency Ratio, and Financial Efficiency Ratio simultaneously have a positive and significant effect on Fiscal Incentive Funds.